ZIONISME YAHUDI DAN TANTANGAN DAKWAH ISLAM - Muhammad Syarif Hasyim (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2012)
Before the birth of the state of Isreael, the Jewish nation was scattered in several countries, particularly in Europe and America. They are in a state of being suppressed, deprivated of political rights, suffering from expulsion and massacre. This condition encourages them to seek a unity. They communicate throuh promoting the issues of nationality and human rights. Thet communicate with the leaders of western countries. For internal consolidation, the Jews utilize religious slogans which they believe. From this emerge a movement called "Zionism", an international religioi-political movement that is successful in gathering the Jews who are scattered in teh world for the sake of the establishment of Jews state in Palestine which is believe as "the promised land of God". Finally, the Jews struggled to carry out diplomatic and political lobbying to officially become a member of the United Nations in 1949. This realitiy requires the Islamic preaching shoul formulate models and methods in orde that the mission which is based on the principle of "mercy to all mankinds" can be really realized and is able to determine the mocdel of world civilization.